Exploring Mediating Role of Supply Chain Management between Logistic Management, Supplier Selection and Planning of Supply Chain and Sustainability, Supported Tourism Business in Indonesia - I Nyoman Sudapet; Agus Sukoco; Mohd Haziman Bin Wan Ibrahim; Muhammad Ikhsan Setiawan (International Journal of Supply Chain Management, 2019)
The competition is mounting in the Indonesian tourism sector. Therefore, it is key for the firms operating in this sector to adopt different strategies related to the supply chain by which they can attain sustainability. Therefore, the objective of this study was to examine the impact of logistic management, supplier selection, and planning of the supply chain on SCM and sustainability of the organization. Moreover, the mediating role of SCM between logistic management, supplier selection, and planning of supply chain and sustainability of the organization. the data was collected from the 258 respondents of the tourism sector on Indonesia in the form of a questionnaire. For data analyses and hypotheses testing, this study has used PLS-SEM as suitable technique. The findings of the study pointed out that all relations to be significant. It means that supply chain functions, Logistic management, Supplier selection on supply chain management, and sustainability. The findings of the study are helpful for the policy makers of this sector to adopt different strategies by which they can attain sustainability.